2016
DOI: 10.18632/aging.100948
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated ageing and renal dysfunction links lower socioeconomic status and dietary phosphate intake

Abstract: BackgroundWe have sought to explore the impact of dietary Pi intake on human age related health in the pSoBid cohort (n=666) to explain the disparity between health and deprivation status in this cohort. As hyperphosphataemia is a driver of accelerated ageing in rodent models of progeria we tested whether variation in Pi levels in man associate with measures of biological ageing and health.ResultsWe observed significant relationships between serum Pi levels and markers of biological age (telomere length (p=0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 38 publications
1
42
1
Order By: Relevance
“…Indeed, human progerias, such as Hutchinson's Guilford's syndrome, or a disease of accelerated ageing, such as CKD, display elevated serum phosphate levels . Epidemiological studies have indicated that frequent consumption of red meat is a source of age‐related hyperphosphataemia in man . This offers a mechanistic basis for age‐related health, inflammatory burden (inflammageing) and alterations in the composition and role of the microbiota.…”
Section: The Ageing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, human progerias, such as Hutchinson's Guilford's syndrome, or a disease of accelerated ageing, such as CKD, display elevated serum phosphate levels . Epidemiological studies have indicated that frequent consumption of red meat is a source of age‐related hyperphosphataemia in man . This offers a mechanistic basis for age‐related health, inflammatory burden (inflammageing) and alterations in the composition and role of the microbiota.…”
Section: The Ageing Processmentioning
confidence: 99%
“…A sub-optimal foodome can lead to an aberrant microbiome with consequential health effects, typically mediated by accelerated ageing, whereby the hallmarks of normative ageing become dysregulated, metabolic morbidity is facilitated and the diseasome of ageing is ensues at an earlier chronological age syndrome, or a disease of accelerated ageing, such as CKD, display elevated serum phosphate levels [44]. Epidemiological studies have indicated that frequent consumption of red meat is a source of age-related hyperphosphataemia in man [46]. This offers a mechanistic basis for age-related health, inflammatory burden (inflammageing) and alterations in the composition and role of the microbiota.…”
Section: The Ageing Processmentioning
confidence: 99%
“…It is a proatherogenic and pro-inflammatory compound that provides a mechanistic link between excess red meat consumption in man linked to both hyperphosphatemia and accelerated aging. 145,149,150 Notably in these studies, less than 25% of inter-individual variation in inflammatory status was explainable by biological age, 143 or methylation levels, 151 which suggest that the microbiome might have a larger impact on inflammation than anticipated based on a pre-existing hypothesis of a linear relationship between biological age and SASP related inflammatory status.…”
Section: Environmental Drivers Of Epigenetic Changes and Age Related mentioning
confidence: 65%
“…Notably, recent evidence has indicated that this is also independently associated with nutritionally-driven hyperphosphatemia, due to frequent red meat and processed meat consumption. 145 These findings are also relevant to the growing incidence of CKD globally and indicate that nutritionally driven hyperphosphatemia associated with lower socioeconomic status and poor eating habits are potential contributory factors to CKD and chronic inflammation. 145 The question then arises how nutritionally acquired phosphate affects the epigenome?…”
Section: Environmental Drivers Of Epigenetic Changes and Age Related mentioning
confidence: 91%
See 1 more Smart Citation